Seguimiento de trayectoria en robótica móvil con alimentación de energía solar - Huayanay Villar, José Luis (2024)
In this work, apply and implement trajectory tracking in mobile robotics powered by solar energy, as well as model, simulate, test and monitor. This includes work or use of sensors, computer hardware and software such as SCILAB, Xcos and use of micro controllers for Automation purposes. The dynamics of the linear servo type plant is presented, the system based on control methods that must be stable and provide an extension that allows unique integrators. Mathematical modeling of the servomechanism, studies and analysis will be carried out in continuous and discrete time, in addition to the implementation of control. The Arduino micro-controller will be used to obtain experimental results. To power the mobile robot for this project, it is necessary to use the energy from solar radiation to convert it into electrical energy through the flow of electrons incident on the semiconductors, which are generally made of silicon, a material widely used in electronics.